Applicability of Darbo's Fixed Point Theorem on the Existence of a Solution to Fractional Differential Equations of Sequential Type. (18th April 2023) - Awadalla, Muath; Abuasbeh, Kinda; Manigandan, Murugesan; Al Ghafli, Ahmed A.; Al Salman, Hassan J.
Abstract : In this article, we study the existence of the solution for the fractional differential equations of sequential type with nonlocal integral boundary conditions. The main results are established with the aid of Darbo's fixed point theorem and Hausdorff's measure of noncompactness method. The stability of the proposed fractional differential equation is also investigated via the Ulam–Hyer technique. In addition, an applied example that supports the theoretical results reached through this study is included.